2022
DOI: 10.1002/nha3.20367
|View full text |Cite
|
Sign up to set email alerts
|

The missing voices of learning and development professionals: Factors influencing formal and informal practices of reverse mentoring

Abstract: There is dearth of studies exploring the likelihood of reverse mentoring practices being accepted or resisted in diverse organizational contexts. Moreover, prior studies on reverse mentoring have focused on the formal programmatic implementations instead of exploring the informal instances where senior employees learn from their junior colleagues in organizations. To address these gaps, we pose the question: What are the factors necessary for formal and informal reverse mentoring to succeed? We utilized a qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Informal reverse mentoring offered an array of benefits in the Chinese higher education context, including increased self‐confidence, a sense of accomplishment, and research engagement among students as well as enhanced professional competence among supervisors. This is similar to previous findings in the workplace where less experienced mentors receive increased job satisfaction and increased engagement, while more experienced mentees gain content knowledge and technical skills (e.g., Chaudhuri, Ghosh, & Park, 2022; Garg et al., 2021; Murphy, 2012). Our data also showed that increased self‐confidence and sense of accomplishment further increased students' willingness to express their own opinions, creating conditions for the next round of reverse mentoring.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Informal reverse mentoring offered an array of benefits in the Chinese higher education context, including increased self‐confidence, a sense of accomplishment, and research engagement among students as well as enhanced professional competence among supervisors. This is similar to previous findings in the workplace where less experienced mentors receive increased job satisfaction and increased engagement, while more experienced mentees gain content knowledge and technical skills (e.g., Chaudhuri, Ghosh, & Park, 2022; Garg et al., 2021; Murphy, 2012). Our data also showed that increased self‐confidence and sense of accomplishment further increased students' willingness to express their own opinions, creating conditions for the next round of reverse mentoring.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Effective reverse mentoring was indeed found in our cases where the supervisor–student relationship was relatively equal: The supervisor was open minded and eager to learn from the students, while the student was daring enough to express competing views or point out errors of the supervisor. This is also consistent with Chaudhuri, Ghosh, and Park's (2022) views on successful reverse mentoring: “the senior mentees do not feel embarrassed to learn from their juniors’ expertise and the junior mentors do not feel inhibited to contribute to their seniors' learning” (p. 15). Our study confirms the crucial role of generational equity in the success of informal reverse mentoring, especially when it takes place in a Chinese undergraduate research supervision context.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, as virtual collaboration platforms have user-friendly interfaces that require minimal technical expertise (Walter-Tscharf, 2022), it was easier for the aged working population to adapt to the technology. With the subscription model, companies do not have to invest in infrastructure, which was not in place or part of the budget during the pandemic [36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Theme #1: Subscription To Virtual Collaboration Platformsmentioning
confidence: 99%